Experimental analysis of a latent heat thermal energy storage unit enhanced by branched fins - Pandiri, Shiva; Murphy, Jacob; Fouladi, Kamran; Tiari, Saeed (Frontiers in Thermal Engineering, 2025)
The global shift towards renewable energy to replace fossil fuels has led to exploring thermal energy storage techniques employing phase change materials (PCM), known as latent heat thermal energy storage (LHTES). Renewable energy sources such as solar and wind have limitations due to their unpredictable nature and thus require adequate storage during times of intermittency. PCMs offer a high energy storage density, however, their thermal performance is limited by their low thermal conductivity. This is leading researchers to investigate passive heat transfer enhancement techniques, such as nanoparticle dispersion, porous matrices, heat pipes, and fins, to improve heat transfer within PCMs. Recent studies have primarily focused on the numerical analysis of branched fins, leaving a significant gap in experimental validation. This study addresses this gap by providing a comprehensive experimental evaluation of the thermal performance of a LHTES system enhanced by branched fins, The performance of various fin configurations is compared during both charging and discharging processes. The present study takes a novel approach in comparing performance of radial fins, Y-fins, and snowflake fins in two sets of cases: four-fin and six-fin arrangements, which are compared to a baseline of a zero-fin configuration. All four-fin arrangements contain the same volume of copper, and all six-fin arrangements contain more copper than the four-fin arrangements. The fin configurations are compared based on charging and discharging times and the system energy response. The comparisons indicate that all branched fins configurations resulted in significant reductions in charging and discharging times compared to the benchmark. For four-fin arrangements, radial fins show a decrease of 81.52% and 63.45%, Y-fins show a reduction of 85.97% and 73.64% and snowflake fins show a reduction of 86.3% and 73.2% in charging and discharging times, respectively. For six-fin arrangements, radial fins show a reduction of 89.76% and 76.87%, Y-fins show a reduction of 91.63% and 83.03%, and snowflake fins show a reduction of 91.61% and 86.14% reduction in charging and discharging times, respectively.